1999
DOI: 10.1159/000054436
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoids and Glucocorticoids Cooperatively Increase Salt Intake and Angiotensin II Receptor Binding in Rat Brain

Abstract: Mineralocorticoids, such as deoxycorticosterone acetate (DOCA), and angiotensin II (AngII) act synergistically in the brain to elicit salt appetite. Glucocorticoids, such as dexamethasone (DEX), also may enhance the behavioral effects of DOCA and AngII. However, the brain regions involved in these behavioral interactions have not been elucidated. This study tested the hypothesis that DEX potentiates the effects of DOCA on AngII binding, especially at the AT1 receptor. We confirmed that DEX potentiated the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 76 publications
1
45
0
Order By: Relevance
“…An important role for the MR is supported by recent data demonstrating that intracerebrovascular infusion of aldosterone reduced the gain of the baroreflex function in Dahl Salt-sensitive rats (4). Cooperative effects of simultaneous MR and GR occupation on angiotensin receptor expression and feedback inhibition of the hypothalamic pituitary adrenal axis have been described by others and could be important for glucocorticoid effects on central cardiovascular regulation (5,45). Furthermore, interactions between MRs and GRs on central cardiovascular regulation could explain some of the inconsistencies in the results of previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…An important role for the MR is supported by recent data demonstrating that intracerebrovascular infusion of aldosterone reduced the gain of the baroreflex function in Dahl Salt-sensitive rats (4). Cooperative effects of simultaneous MR and GR occupation on angiotensin receptor expression and feedback inhibition of the hypothalamic pituitary adrenal axis have been described by others and could be important for glucocorticoid effects on central cardiovascular regulation (5,45). Furthermore, interactions between MRs and GRs on central cardiovascular regulation could explain some of the inconsistencies in the results of previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…The strongest evidence for glucocorticoid regulation of salt appetite came from studies examining NaCl intake and angiotensin II-receptor binding after administration of DOC and dexamethasone (Shelat et al, 1999b). Specifically, rats treated with DOC and dexamethasone consumed more NaCl than when given DOC alone.…”
Section: Central Interactions Of Aldosterone and Angiotensin IImentioning
confidence: 99%
“…The sites of action of ANG II that affect the sympathetic neural outflow could not be determined from the present study, but evidence from previous studies has suggested the involvement of the central nervous system (7,21,24,26,27,34,37) or sympathetic ganglia (3,10,11). The effect of circulating ANG II on the sympathetic nervous system has been postulated to be mediated via circumventricular organs, including the area postrema or the subfornical organs, which are regions that have no blood-brain barrier (7,21,24,26,27,34,37).…”
Section: Discussionmentioning
confidence: 56%
“…A possible explanation for the enhanced pressor response to ANG II observed in PA patients is an upregulation of ANG II receptors in the vasculature (31,32) and in the central and peripheral components of the sympa- (31,32) and in the brain (5,34,37), and then it induces an upregulation of ANG II receptors. Another possible explanation for the exaggerated pressor response to ANG II in PA patients is in part due to an elevation of serum sodium concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation